Dietary N-Carbamylglutamate Supplementation Boosts Intestinal Mucosal Immunity in Escherichia coli Challenged Piglets - Zhang, Fengrui (Public Library of Science, 2013)
N-carbamylglutamate (NCG) has been shown to enhance performance in neonatal piglets. However, few studies have demonstrated the effect of NCG on the intestinal mucosal barrier. This study was conducted to determine the effects of dietary NCG supplementation on intestinal mucosal immunity in neonatal piglets after an Escherichia coli (E. coli) challenge. New-born piglets (4 d old) were assigned randomly to one of four treatments (n = 7), including (I) sham challenge, (II) sham challenge +50 mg/kg NCG, (III) E. coli challenge, and (IV) E. coli challenge +50 mg/kg NCG. On d 8, pigs in the E. coli challenge groups (III and IV) were orally challenged with 5 mL of E. coli K88 (10(8) CFU/mL), whereas pigs in the sham challenge groups (I and II) were orally dosed with an equal volume of water. On d 13, all piglets were sacrificed, and samples were collected and examined. The results show that average daily gain in the E. coli challenged piglets (III and IV) was decreased (P(E.coli)<0.05). However, it tended to be higher in the NCG treated piglets (II and IV). Ileum secretory IgA, as well as IFN-γ, IL-2, IL-4 and IL-10 in ileal homogenates, were increased in E. coli challenged piglets (III and IV). Similarly, ileum SIgA and IL-10 levels, and CD4(+) percentage in NCG treated piglets (II and IV) were higher than no-NCG treated piglets (P(NCG)<0.05). However, the IL-2 level was only decreased in the piglets of E. coli challenge + NCG group (IV) compared with E. coli challenge group (III) (P<0.05). No change in the IL-2 level of the sham challenged piglets (III) was observed. In conclusion, dietary NCG supplementation has some beneficial effects on intestinal mucosal immunity in E. coli challenged piglets, which might be associated with stimulated lymphocyte proliferation and cytokine synthesis. Our findings have an important implication that NCG may be used to reduce diarrhea in neonatal piglets.